Customer Satisfaction as a Bridge Between Service Quality, Brand Image, and Loyalty: A Case Study of Eyelash Extensions in Bandung - Yunengsih, Neng; Munawar, Fansuri (Dinasti International Journal of Education Management and Social Science, 2025)
Green branding involving public figures is increasingly  shaped by digital dramaturgy and multimodal strategies that construct ecological personas. This research investigates the influence of service quality and brand image on customer loyalty, with particular emphasis on the mediating role of customer satisfaction in the context of eyelash extension services at Beauty Bar D’Stylashes in Bandung. Using a quantitative approach, data were collected from 200 participants through structured questionnaires and analyzed using SEM-PLS with SmartPLS 4.0. The findings reveal that both service quality and brand image significantly affect customer satisfaction, which in turn plays a crucial role in mediating and enhancing customer loyalty. Among the three variables, customer satisfaction emerged as the most influential factor in fostering loyalty. While service quality has a direct impact on satisfaction, brand image contributes more strongly through its indirect effect via satisfaction. These results underscore the importance of consistently delivering high-quality service and cultivating a compelling, emotionally engaging brand image to build lasting customer loyalty. For businesses in the beauty industry, enhancing customer satisfaction is not